Propuesta de mejora a los procesos de gestión trabajo de año de la ESPAM MFL - Rendón Muñoz, Valeria Liseth (2018)
This research project has the objective of proposing improvements to the process management of the year's work of the Escuela Superior Politécnica Agropecuaria de Manabi Manuel Félix López, through the application of the technique of measurement of times, with the purpose of finding guidelines that allow to improve its quality and the performance of each one of the actors involved. The methods that were applied included: the inductive method that allowed to obtain the main problems starting from the particular to the general. The analytical method helped to carry out an analysis of each one of the activities that are developed in the mentioned process. The deductive method that allowed to indicate the main ideas of the processes to study. Techniques were then applied to this research project such as observation and interview, which helped to graphically represent the processes, showing clearly and easily the trajectory of them. Then the technique of time analysis was applied to this project, allowing to identify the activities that do not generate value to the process. In this way the proposal of a plan of improvements with ideas of action is born that contribute to counteract unnecessary activities in the process, optimizing time, resource and at the same time obtaining better results.